2002
DOI: 10.1111/j.1945-5100.2002.tb00856.x
|View full text |Cite
|
Sign up to set email alerts
|

Thermoluminescence sensitivity and thermal history of type 3 ordinary chondrites: Eleven new type 3.0–3.1 chondrites and possible explanations for differences among H, L, and LL chondrites

Abstract: Abstract-We review induced thermoluminescence (TL) data for 102 unequilibrated ordinary chondrites (UOCs), many data just published in abstracts, in order to identify particularly primitive DOCs and further explore TL systematics that may have implications for the history ofthe chondrites and their parent body. We have identified 11 DOCs ofpetrologic types 3.0-3. These samples represent an important new resource for researchers interested in the nature ofprimitive solar system materials. Previously reported tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 43 publications
0
20
0
Order By: Relevance
“…The differences between the determined petrographic types are weaker for reduced than for oxidised CV3s. The ITL signal originates from the feldspar formed by the devitrification of mesostasis glass during metamorphism (Sears et al, 1980;Brearley and Jones, 1998;Benoit et al, 2002), and was initially developed on Ordinary Chondrites that suffered weak or negligible aqueous alteration (Grossman et al, 2000). On the other hand, oxidised CV3 chondrites suffered major aqueous alteration that led to dissolution of mesostasis glass and feldspars, explaining why the petrologic subtypes of these objects are systematically underestimated.…”
Section: Attribution Of Petrologic Types To Cv3s By Comparison With Uocsmentioning
confidence: 97%
See 1 more Smart Citation
“…The differences between the determined petrographic types are weaker for reduced than for oxidised CV3s. The ITL signal originates from the feldspar formed by the devitrification of mesostasis glass during metamorphism (Sears et al, 1980;Brearley and Jones, 1998;Benoit et al, 2002), and was initially developed on Ordinary Chondrites that suffered weak or negligible aqueous alteration (Grossman et al, 2000). On the other hand, oxidised CV3 chondrites suffered major aqueous alteration that led to dissolution of mesostasis glass and feldspars, explaining why the petrologic subtypes of these objects are systematically underestimated.…”
Section: Attribution Of Petrologic Types To Cv3s By Comparison With Uocsmentioning
confidence: 97%
“…A first set of measurements was composed of a series of UOCs with well known petrographic types (Sears et al, 1980;Sears et al, 1991b;Benoit et al, 2002) In BSE images, no zoning of olivine phenocrysts is observed for objects of petrographic types ranging between 3.0 and 3.2 (Fig. 7a).…”
Section: Zoning Of Olivine Phenocrystsmentioning
confidence: 99%
“…However, measured thermoluminescence sensitivity of feldspars indicates that this transition occurs at lower temperatures, by petrologic type 3.5 (Sears et al. 1982; Benoit et al. 2001, 2002).…”
Section: Evaluation Of Pyroxene and Plagioclase Geothermometrymentioning
confidence: 99%
“…QUE 97008 was originally classified as L3.4 with a weathering grade of A (Grossman 1999). Benoit et al. (2002) recommended a petrologic type 3.0 for QUE 97008 based on thermoluminescence properties, whereas Grossman and Brearley (2005) suggested a petrologic type of 3.05 based on petrographic characteristics.…”
Section: Samples and Analytical Conditionsmentioning
confidence: 99%